2017
DOI: 10.1111/sji.12500
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Tolerance. Part I of a Report of a Workshop on Foundational Concepts of Immune Regulation

Abstract: This report, the first of two, arose from a one-week workshop directed at discussing concepts of immune regulation, and focuses on immunological tolerance. We first outline the major ideas we thought sufficiently plausible to provide a context for discussing more controversial issues around tolerance. We then report on our discussion of different experiments that appear paradoxical in terms of the different, contemporary models of CD4 T cell inactivation/activation, and how such observations might be resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…The authors concluded that the degree of antigenic disparity, among other factors, governs the ability of transplants to induce immunity and that, in the absence of sufficient disparity, tolerance ensues (41). These observations are consistent with the Quorum Hypothesis, even though it is unclear whether rejection requires a quorum of CD8, a quorum of CD4 T cells, or a quorum of a combination of the two types of T cells (42). The observations reported are not readily accounted for by the Danger Model, as this model posits that whether Ag activates/inactivates T cells depends upon whether danger is present/absent rather than the degree of foreignness of the Ag (42).…”
Section: Further Observations Pertinent To the Quorum Hypothesis For mentioning
confidence: 82%
“…The authors concluded that the degree of antigenic disparity, among other factors, governs the ability of transplants to induce immunity and that, in the absence of sufficient disparity, tolerance ensues (41). These observations are consistent with the Quorum Hypothesis, even though it is unclear whether rejection requires a quorum of CD8, a quorum of CD4 T cells, or a quorum of a combination of the two types of T cells (42). The observations reported are not readily accounted for by the Danger Model, as this model posits that whether Ag activates/inactivates T cells depends upon whether danger is present/absent rather than the degree of foreignness of the Ag (42).…”
Section: Further Observations Pertinent To the Quorum Hypothesis For mentioning
confidence: 82%
“…The binding of diverse ligands to the diverse variable regions of antibodies would have to cause the same structural change in the constant regions; otherwise, separate interaction sensing units would have to evolve that recognize each possible structural change, which is implausible. Given the high diversity of variable regions and given that antibody genes are assembled somatically, it is difficult to envisage how an allosteric mechanism can evolve that allows the same structural change to be induced in different antibodies on binding all ligands . Similar considerations apply to signalling by mIg of B cells and the TcR of T cells.…”
Section: Allosteric Mechanisms Are Implausible As a Signalling Mechanmentioning
confidence: 99%
“…As illustration, let us look at the extent to which Bretscher's proposal of a two-step two-signal model for the activation of iTh (in his nomenclature, pTh or na€ ıve Th) solves these two problems (see Figure 1 in ref. [1]).…”
Section: The Views Of the Workhop Participantsmentioning
confidence: 99%